The Role of Social Protection in Building, Protecting, and Deploying Human Capital in the East Asia and Pacific Region - Moroz, Harry Edmund (World Bank, Washington, DC, 2020)
The objective of this note is to highlight how social protection can help lay the human capital foundations needed for poverty reduction and economic growth in the East Asia and Pacific region while also building, protecting, and deploying the human capital needed to keep up with and take advantage of technological and demographic developments. The note first introduces the human capital development challenge in the region in the context of the World Bank’s Human Capital Project. The note then discusses social protection policies that relate directly to the Human Capital Index, a cross-country indicator of progress on human capital that focuses on the early and school-age years. The final part of the note discusses social protection policies relevant to the broader aim of the Human Capital Project to initiate engagement with client countries about how human capital can be accumulated, protected, and deployed throughout the entire lifecycle. The note considers the potential impacts of the COVID-19 outbreak on human capital, but frames the discussion of social protection and human capital broadly to identify implications relevant to the outbreak but also beyond it